A One-Step Reverse Transcription PCR Assay for the Detection of Transmissible Gastroenteritis Virus Genome in Pigs - Fateh Singh; Katherukamem Rajukumar; Dhanapal Senthilkumar; Govindarajulu Venkatesh; Gopal Sarkar; Jaswant Patel; Rohit Sahu; Nourin Khan; Atul Kumar Pateriya; Vijendra Pal Singh; Aniket Sanyal (Journal of Pure and Applied Microbiology)
The study focused on developing an indigenous, one-step reverse transcription (RT)-PCR assay for detecting the porcine transmissible gastroenteritis virus (TGEV) genome. In summary, a gene construct and two sets of primers were designed by aligning N gene sequences from various TGEV strains, which were subsequently synthesized. The gene construct was sub-cloned into the pTZ57R/T vector, enabling the synthesis of in vitro transcribed (IVT) RNA, which served as a TGEV-positive control for RT-PCR protocol optimization. The assay optimization involved systematic testing of various parameters, including primer concentrations, magnesium (Mg++) levels, RNA template quantities, annealing temperatures, and other thermal variables. The analytical sensitivity was evaluated by examining serial 10-fold dilutions of IVT-RNA, both in actual form and when recovered from swine feces after spiking with the same dilutions of IVT-RNA. The developed assay demonstrated analytical sensitivities of 47.548 × 10² and 24.629 × 10³ RNA copies at 10-7 and 10-6 dilutions of IVT-RNA and spiked fecal RNA, respectively. Specificity was confirmed by testing against porcine epidemic diarrhea virus (PEDV), porcine reproductive and respiratory syndrome virus (PRRSV), classical swine fever virus (CSFV), swine influenza virus (SIV), and known TGEV-negative swine fecal or rectal swab samples (n = 320) collected from the field. The assay exhibited specific amplification for TGEV without cross-reactivity to PEDV, PRRSV, CSFV, SIV, or field samples. This one-step RT-PCR assay proved to be both sensitive and specific for TGEV genomic detection, offering a reliable diagnostic tool for future outbreaks and subsequent monitoring of TGE.